A modified cross antenna rotation and inversion algorithm for Peak-to-Average Power Ratio Reduction in MIMO-OFDM systems - Janad, Mohanat; Al-Khateeb, Wajdi Fawzi Mohammed; Habaebi, Mohamed Hadi (penseejournal.com, 2013)
In this work, a Modified Cross Antenna Rotation and Inversion algorithm is introduced to reduce the high Peak to Average Power Ratio (PAPR) of the MIMO-OFDM signals. Cross Antenna Rotation and Inversion (CARI) and its derivative (SS-CARI) are considered to be very effective methods to reduce high PAPR; however, (CARI) algorithm suffers high complexity in computational operations and the (SS-CARI) which does not utilize the degrees of freedom in any domain. Hence, the Modified CARI comes to its place in which, it has less computational complexity and can fully utilize the degrees of freedom in space domain to overcome the shortage of Successive Suboptimal Cross-Antenna Rotation and Inversion (SS-CARI) algorithm, moreover, it achieves permutations of Sub-blocks in frequency domain, So it can fully use the degrees of freedom in both space domain and frequency domain. Finally, it has two antennas at both uplink and downlink terminals which reduces the need for more Side Information (SI). Simulation results shows that the effect of PAPR reduction of introduced modified method is better than original CARI algorithm. Furthermore, as the number of Sub-blocks M increases, the results are getting better.